Oceanographic Indicators of Seasonal Variability in the Guajira Upwelling System and Their Relationship with Phytoplankton - Jhon Carlos Salon-Barros; Rafael Ricardo Torres-Parra; Digna Rueda-Roa; Frank Muller-Karger (Oceans, 2026)
The Guajira Upwelling System (GUS) is located between 10–12.5° N and 61–75.5° W in the Southern–Central Caribbean Sea. This study examines its spatial and seasonal variability using upwelling indices derived from surface differences in temperature, salinity, density, and absolute dynamic topography between the GUS and a nearby Caribbean region (78–68° W, 10–16° N) not affected by coastal upwelling. Weekly time series from 1998 to 2022 were analyzed. The difference-based indices were compared with Ekman transport, a conventional proxy for upwelling intensity, and with satellite-derived chlorophyll-a to evaluate the phytoplankton response. Seasonal cycles were further examined at four representative grid points along the system. Among the indices, sea surface temperature most effectively delineated the spatial extent and seasonal variability of the GUS. Comparisons with chlorophyll-a revealed a strong upwelling–biomass relationship in the northern sector (east of 73.5° W), whereas productivity in the southern sector was not primarily driven by coastal upwelling. Correlation maps indicated that the weakening of upwelling influence coincided with the region affected by the Magdalena River plume.

Heat vulnerability in the City of Ponce, Puerto Rico - Laura T. Cabrera-Rivera; Frank E. Muller-Karger; Digna Rueda-Roa; Heriberto Marin; Tischa A. Muñoz-Erickson; Pablo A. Méndez-Lázaro (Urban Climate, 2026)

Introduction to the Special Issue on A Vision for Capacity Sharing in the Ocean Sciences - Ellen Kappel; Brian Arbic; Johanna Diwa-Acallar; Nicolas Moity; José Muelbert; Frank Muller-Karger; Olubunmi Nubi; Digna Rueda-Roa; Aileen Tan Shau Hwai (Oceanography, 2025)

Water quality observations in the marine aquaculture complex of the Deeba Triangle, Lake Manzala, Egyptian Mediterranean coast - Mahmoud M. El-Mezayen; Digna T. Rueda-Roa; Mohamed A. Essa; Frank E. Muller-Karger; Ahmed E. Elghobashy (Environmental Monitoring and Assessment, 2018)

Description and Mechanisms of the Mid-Year Upwelling in the Southern Caribbean Sea from Remote Sensing and Local Data - Digna Rueda-Roa; Tal Ezer; Frank Muller-Karger (Journal of Marine Science and Engineering, 2018)
The southern Caribbean Sea experiences strong coastal upwelling between December and April due to the seasonal strengthening of the trade winds. A second upwelling was recently detected in the southeastern Caribbean during June–August, when local coastal wind intensities weaken. Using synoptic satellite measurements and in situ data, this mid-year upwelling was characterized in terms of surface and subsurface temperature structures, and its mechanisms were explored. The mid-year upwelling lasts 6–9 weeks with satellite sea surface temperature (SST) ~1–2° C warmer than the primary upwelling. Three possible upwelling mechanisms were analyzed: cross-shore Ekman transport (csET) due to alongshore winds, wind curl (Ekman pumping/suction) due to wind spatial gradients, and dynamic uplift caused by variations in the strength/position of the Caribbean Current. These parameters were derived from satellite wind and altimeter observations. The principal and the mid-year upwelling were driven primarily by csET (78–86%). However, SST had similar or better correlations with the Ekman pumping/suction integrated up to 100 km offshore (WE100) than with csET, possibly due to its influence on the isopycnal depth of the source waters for the coastal upwelling. The mid-year upwelling was not caused by dynamic uplift but it might have been enhanced by the seasonal intensification of the Caribbean Current during that period.